The perceptions of university students with regard to the perceived professional competencies for the educational counselor - a factorial study (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed at identifying the perceptions of university postgraduate students with regard to the factorial structure related to the perceived professional competencies for the educational counselor. The researcher employed the descriptive correlation method, and the instrument was developed so as to measure the professional competencies for the educational counselor; the content validity as well as the reliability for the instrument were verified. The study sample consisted of (175) male and female students from the students of postgraduate studies at Mu'tah University and Students for in Israa Private university. The results showed that the first factor consisted of 8 items relating to the skill of counseling interview using the appropriate counseling methods, good planning, managing the session, using the accurate professional counseling language, as well as the suitable use of the current technology ' mobiles- Facebook - and the internet'. I suggest that this factor could be labeled as the applied professional competencies. The second factor also consisted of 8 items relating to the skill of interaction , effective communication, leadership, decision-making, tolerance, honesty in communication, respect for difference in attitudes , and supporting the self-worth of people; thus I suggest that this factor could be labeled the administrative professional competencies. The third factor consisted of 6 items relating to the skill of observation, gathering and analyzing data, writing a psychological report, as well as measuring and evaluating behavior; and so I suggest that this factor could be labeled the evaluative professional competencies. The results showed that all correlations are statistically significant at the level of significance (α≤ 0.05), both with regard to the level of correlation with the dimension as well as the total score or at the level of the relational matrix, and that there are apparent differences in the estimation of the study sample individuals for the traits of educational counselor according to the study variables ( gender, major, and institution type); while the results didn't show any differences due to the study variables of ( gender, specialization, and institution type) in the perceptions of university students with regard to the professional competencies for the educational counselor.